Geographical Economics and the Role of Pollution on Location - Charles van Marrewijk (Tinbergen Institute, 2005)
Geographical economics analyzes the endogenous determination of the location of economic activity in a general equilibrium framework. We investigate the impact of pollution by focusing on the interaction between location advantages and negative pollution externalities associated with local production. We distinguish between two goods (food and manufactures) and two factors of production (mobile human capital and immobile unskilled labor) and show that agglomeration of economic activity tends to become less attractive with pollution, and thus less likely. Moreover, we provide a simple necessary and sufficient condition for the spreading of economic activity to become more attractive, and thus more likely.
Keywords: F0; Q0; R0; 330; Geographical Economics; Pollution; Location; Umweltbelastung; Regionales Cluster; Betrieblicher Standort; Regionalökonomik